Ugięcia Płyt Ortotropowych o Zmiennych Sztywnościach i Pewnych Nieciągłych Warunkach Brzegowych - Bojda, K.H. (Engineering Transactions, 1971)
The paper contains the formally exact solution of the differential equation of bending of a plate which rests on an elastic foundation, in the case when the rigidities and the foundation coefficient are polynomials of the single variable y; the edges x = 0 and x = a of the plate are simply supported, the boundary conditions along the edge y = 0 being discontinuous. The solution has the form of a double polynomial – trigonometric series. The coefficients of the series are obtained from simple recurrent formulae and from infinite systems of algebraic equations. The solutions are presented concerning continuous plates resting: on elastic supports. The possibility is indicated of obtaining simple solutions in the cases of infinite and semi-infinite plate strips. The solution is derived by means of the algebraic derivative.